Prospective study of association of uterine atonicity and serum calcium levels - HL, Premalahta; Krishnegowda, Raghupathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Uterine atony is one of the leading causes of maternal morbidity and mortality. Uterine atony and PPH is a life threatening condition. The oxytocic drugs increase uterine tone by increasing intracellular calcium. Optimum levels of calcium are very important for the effective uterine contraction. Objective of this study was to correlate the serum calcium levels and uterine atonicity and PPH in women admitted in 1st and 2nd stage of labor in tertiary care hospital like Sri Chamarajendra hospital Hassan institute of medical sciences, Karnataka, India. Methods: Study design is case control study in department of OBG Sri Chamarajendra hospital Hassan. Duration of study is from July 2014 to 2015. Number of subjects studied 200 groups A with serum calcium less than 8 mg% and uterine atony. Group B with serum calcium between 8-10.4 mg% and uterine atony, after vaginal delivery or caesarian delivery. Features of atonicity: soft distended uterus with lack of muscle tone. Results: Total 200 clients were studied. 100 clients with serum calcium >8 mg% and 100 clients with serum calcium <8 mg%. In women with serum calcium <8 mg%, 24 patients developed uterine atonicity. In women with serum calcium > 8 mg% only one client developed uterine atonicity. Conclusions: Our result revealed that low calcium level is strongly associated with uterine atony, hence is a risk factor for uterine atony.